Pengaturan Hukum Laut Internasional Terhadap Tabrakan Kapal Yang Di Sengajakan - Heatubun, Alowisya Natalia; Anwar, Arman; Wattimena, Josina Augustina Yvonne (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: Indonesia is an archipelagic country that has a very wide coastline and sea in the world and is rich in marine resources that must be protected, however, its strategic location and busy shipping by foreign ships makes Indonesia also an international shipping lane which is prone to ship accidents. . One of the causes of ship accidents is human error.Purposes of the Research: This writing aims to examine and find out the arrangements regarding the prohibition of intentionally crashing ships based on international law provisions, examine and find out the forms of state responsibility that violate the provisions of international law, and this research as one of the requirements for writing a thesis in obtaining a Bachelor of Laws degree at the Faculty Pattimura University Law. Methods of the Research: Normative Juridical research method, namely obtaining data from the library in the form of documents, books, magazines and other literature related to writing. The source of legal material used is Primary legal material, Secondary legal material, and Tertiary legal material and used as a technique for collecting legal material, then processing and analyzing legal material through qualitative analysis, namely the data obtained is then systematically arranged for further qualitative analysis based on scientific disciplines. civil law to achieve clarity of issues to be discussed.Results of the Research: The results of the study show that international conventions governing ship safety and shipping security include SOLAS (Safety Of Life At Sea) 1974, MARPOL (Marine Pollition) 1973/1978 and Load Line Convention 1966 and Collreg 1972 (Collision Regulation) as well as national law. Indonesia does not implicitly contain legal norms aimed at intentional ship collisions. This is because the purpose of establishing these legal provisions is precisely to anticipate the occurrence of ship collisions due to human error in the perspective of negligence or negligence. Even so, explicitly the legal logic is that if an unintentional act can be punished then especially if it is done intentionally. The impact of the losses incurred has legal consequences of course on the responsibilities of the flag state as well as captains and shipping companies to the aggrieved party, including in this case the coastal state.